Aplikasi Deteksi Tepi pada Realtime Video menggunakan Algoritma Canny Detection - Edy Winarno (Dinamik, 2011)
Real-time video and image processing is used in a wide variety of applications from video surveillance and traffic management to medical imaging applications. This paper presents the implementation of an canny edge-detection using in realtime video from camera. The Canny algorithm uses an optimal edge detector based on a set of criteria which include finding the most edges by minimizing the error rate, marking edges as closely as possible to the actual edges to maximize localization, and marking edges only once when a single edge exists for minimal response.